Cooperative Rare‐Earth/Lithium‐Mediated Conversion of White Phosphorus. Issue 22 (16th March 2023) - You, Qing; Zhang, Jie; Zhang, Fangjun; Cai, Jiamin; Zhou, Xigeng
Abstract: The rare‐earth/lithium cooperative effect on functionalization of white phosphorus has been investigated. The reaction of diazabutadiene‐supported yttrium hydride chelated a LiPPh2 molecule (LY ⋅ THF)2 ( μ ‐H)2 [ μ ‐PPh2 (Li)] (1, L=N, N'‐di(2, 6‐diisopropylphenyl)‐1, 4‐diazabutadiene) with P4 gave two novel mixed Y/Li multinuclear polyphosphorus complexes (LY ⋅ THF)2 [ cyclo ‐P3 ]Li(THF)3 (2 ) and [Li(THF)4 ] + [(LY ⋅ THF)3 ( norborane ‐P7 )Li(THF)] − (3 ), accompanied with the elimination of diphosphorus compound Ph2 PPPh2 (4 ) and H2 . However, the comparative reaction of yttrium hydride (LY ⋅ THF)2 ( μ ‐H)2 with P4 afforded a trinuclear yttrium pyramid‐P4 complex (LY ⋅ THF)3 ( μ 3 ‐P(PH)3 ) (5 ). Further investigations show that 5 cannot continuously react with LiPPh2 to form 2 and 3, and LiPPh2 reacted with P4 to form a Zintl ‐P7 lithium complex (TMEDA⋅Li)3 ( Zintl ‐P7 ) (6 ) and 4 . These results indicated that the cooperation of Y/Li for activation of P4 is a key for the formation of 2 and 3 . All new compounds have been characterized by NMR spectroscopy and single‐crystal X‐ray diffraction studies. Abstract : Two heterometal polyphosphorus compounds with cyclo ‐P3 and norborane ‐P7 skeletons were formed by intramolecular cooperative yttrium hydride/LiPPh2 mediated activation of P4, while a pyramid‐like P(PH)3 moiety was constructed from P4 functionalization using single metal specie (LY ⋅ THF)2 ( μ ‐H)2 .